Partial regularity of strong local minimizers of quasiconvex integrals with (p,q)-growth - Schemm, Sabine; Schmidt, Thomas (Proceedings of the Royal Society of Edinburgh Section A-Mathematics, 2009)
We consider strictly quasiconvex integrals in the multi-dimensional calculus of variations. For the C2-integrand f : Nn we impose (p, q)-growth conditions with , > 0 and 1 < p q < min p + 1/n, p(2n 1)/(2n 2). Under these assumptions we prove partial C1,loc- regularity for strong local minimizers of F and the associated relaxed functional F. © 2009 Copyright Royal Society of Edinburgh.
UnivIS-Import:2015-03-09:Pub.2009.nat.dma.lma2.partia_3